Zinc uptake and yield of wheat as influenced by zinc fertilizer in Central Brahmaputra Valley Zone of Assam, India - SAIKIA, T.P.; ZAMAN, A.S.N.; BORDOLOI, P.K.; BORAH, NILAY (Journal of Soil and Water Conservation, 2022)
Field experiment was conducted at AAU-Regional Agricultural Research Station, Shillongani, Nagaon, Assam during 2014-15 to 2016-17 rabi season to evaluate the Zn uptake and yield of wheat (variety CBW 38) in response to Zn-fertilization complemented with recommended dose of fertilizers (RDF). Zinc was applied as ZnSO4.7H2O to the soil at 0, 5, 10, 15, 20 kg ha-1. The treatments were compared with foliar spray (0.5%) with or without soil application (10 kg ha-1) of Zn, both as ZnSO4.7H2O, RDF without Zn and ½RDF-vermicompost (2 t ha-1) instant mixture (comlizer). The grain yield increased significantly with soil application of ZnSO4 up to 15 kg ha-1. The foliar spray of ZnSO4.7H2O (0.5%) alone was not effective, but the same combined with soil application significantly increased grain yield of wheat and was at par with ZnSO4.7H2O 15 kg ha-1. The highest Zn uptake by wheat was recorded with application of 15 kg ha-1 ZnSO4.7H2O, which also gave highest net economic return of wheat production.